Pengaruh Ukuran Asset, Piutang, Utang, Modal Sendiri, dan Anggota terhadap Kinerja Keuangan dan Kebijakan SHU (Studi pada Koperasi Kredit Anggota Puskopdit Flores Mandiri) - Kristoforus Tere; Ubud Salim; Achmad Helmy Djawahir (Jurnal Aplikasi Manajemen, 2015)
Abstract: This study aims to analyze the influence of assets, receivables accounts, debt, equity, number of members on the financial performance and SHU policy by using positivist approach. The population of this study are 45 credit unions, while the samples are the member of Puskopdit Flores Mandiri which are eligible 1000 members, has a greater asset equal to one billion, has held an annual meeting of members, as well as having financial data and complete membership 2008–2013. Analysis technique used a path analysis, supported by qualitative information by nine (9) informants who had worked more than 5 years, with in-depth interview technique. The results showed that the direct effect of test size assets, receivables accounts, equity, and a number of members have a significant effect on financial performance, while debt has a significant negative effect. Testing the direct effect of size assets, receivables accounts, and financial performance have a positive significant effect on net income policies, whereas the debt, equity, and number of significant negative effect on the net income policy. The results showed that all eleven hypotheses that the direct effect of having built a significant effect on the financial performance and net in come policies, had been proven. The testing of the indirect effect of financial performance as an intervening variable mediating the effect of five variables in detecting exogenous to net in come policies from the five hypotheses are built shows that increasing size assets, receivables accounts, equity and total members proved to increase the net in ome policies with a total value greater than the value of the coefficient of influence directly. While the debt does not affect the probability value is greater than the direct effect. In general, the determinants of the total for the first model and the second model of 0,821 or 82,1% of the models can account for the effects of exogenous variables on endogenous variables, while 17,9% is due to other factors outside of research. Thus, the constructs were constructed in this study is perfect instrumental in identifying the contribution of size assets, receivables accounts, debt, equity, and members of the financial performance and net income policy. We found that the indirect effect models constructed show that the debt is not significant because the value is smaller than the direct effect. This suggests there are other factors that have not been found in this study and become a recommendation for further research.Keywords: credit union, size asset, receivable accounts, debt, equity, members, financial performance, net in come policy, Puskopdit Flores Mandiri